2016
DOI: 10.1186/s13068-016-0678-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by the hyperthermophilic bacterium Thermotoga maritima part I: effects of sulfured nutriments, with thiosulfate as model, on hydrogen production and growth

Abstract: Background Thermotoga maritima and T. neapolitana are hyperthermophile bacteria chosen by many research teams to produce bio-hydrogen because of their potential to ferment a wide variety of sugars with the highest theoretical H2/glucose yields. However, to develop economically sustainable bio-processes, the culture medium formulation remained to be optimized. The main aim of this study was to quantify accurately and specifically the effect of thiosulfate, used as sulfured nutriment model, on T. maritima growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 73 publications
3
15
2
Order By: Relevance
“…If this toxicity was sufficient to inhibit growth, it could be used to select for mutants that overcame this effect. Since an increase in H 2 partial pressure shifts the metabolism of T. maritima toward lactate synthesis (6,36,37) and not ethanol, transient inactivation of lactate dehydrogenase (encoded by ldh) could exacerbate H 2 toxicity by blocking lactate formation. This would remove one pathway for excretion of excess reductant and thereby create selective pressure to recover such mutants without having to add exogenous H 2 .…”
Section: Isolation Of H 2 -Resistant and H 2 -Overproducing Cell Linementioning
confidence: 99%
“…If this toxicity was sufficient to inhibit growth, it could be used to select for mutants that overcame this effect. Since an increase in H 2 partial pressure shifts the metabolism of T. maritima toward lactate synthesis (6,36,37) and not ethanol, transient inactivation of lactate dehydrogenase (encoded by ldh) could exacerbate H 2 toxicity by blocking lactate formation. This would remove one pathway for excretion of excess reductant and thereby create selective pressure to recover such mutants without having to add exogenous H 2 .…”
Section: Isolation Of H 2 -Resistant and H 2 -Overproducing Cell Linementioning
confidence: 99%
“…In our study, the growth rate of T. maritima could not be evaluated. However, recent studies showed that it depends on glucose, yeast extract, thiosulfate and dissolved hydrogen concentrations (Boileau et al, 2016;Auria et al, 2016).…”
Section: Constituentmentioning
confidence: 99%
“…In recent years, pure cultures of Thermotoga maritima have attracted considerable interest for their potential to produce hydrogen from many simple and complex carbohydrates (Huber et al, 1986;Chhabra, 2003;Nguyen et al, 2008;Boileau et al, 2016). This bacterium contains a wide range of thermostable hydrolytic enzymes (cellulases, invertase and xylanases), which are important for hydrolyzing the carbohydrate polymers into monomer sugars (Cappelletti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The bioelectrochemical system was connected to a semi-automated platform previously described (Boileau et al 2016) to control the composition and rate of gas input (H 2 , CO 2 , O 2 , N 2 ) with mass flowmeters (Bronkhorst, Netherlands). A continuous monitoring of output gas composition (H 2 , N 2 , CH 4 , O 2, CO 2 ) were performed using a micro-GC equipped with a catharometric detector (MS5A, SRA Instrument, France) and a CARBOCAP CO 2 probe (Vaisala GMT 221, Finland).…”
Section: Semi-automated Bioelectrochemical Systemsmentioning
confidence: 99%